Automatic atrial capture device control in real‐life practice: A multicenter experience. Issue 2 (11th July 2016) - Giammaria, Massimo; Quirino, Gianluca; Alberio, Mariangela; Parravicini, Umberto; Cipolla, Eliana; Rossetti, Guido; Ruocco, Antonio; Senatore, Gaetano; Rametta, Francesco; Pistelli, Paolo
Abstract: Background: Device‐based fully automatic pacing capture detection is useful in clinical practice and important in the era of remote care management. The main objective of this study was to verify the effectiveness of the new ACAP Confirm® algorithm in managing atrial capture in the medium term in comparison with early post‐implantation testing. Methods: Data were collected from 318 patients (66% male; mean age, 73±10 years); 237 of these patients underwent device implantation and 81 box changes in 31 Italian hospitals. Atrial threshold measurements were taken manually and automatically at different pulse widths before discharge and during follow‐up (7±2 months) examination. Results: The algorithm worked as expected in 73% of cases, considering all performed tests. The success rate was 65% and 88% pre‐discharge and during follow‐up examination ( p <0.001), respectively, in patients who had undergone implantation. We did not detect any difference in the performance of the algorithm as a result of the type of atrial lead used. The success rate was 70% during pre‐discharge testing in patients undergoing device replacement. Considering all examination types, manual and automatic measurements yielded threshold values of 1.07±0.47 V and 1.03±0.47 V at 0.2‐ms pulse duration ( p =0.37); 0.66±0.37 V and 0.67±0.36 V at 0.4 ms ( p =0.42); and 0.5±0.28 V and 0.5±0.29 V at 1 ms ( p =0.32). Conclusions: The results show that the algorithm works before discharge, and its reliability increases over the medium term. The algorithm also proved accurate in detecting the atrial threshold automatically. The possibility of activating it does not seem to be influenced by the lead type used, but by the time from implantation.